Análise de processos hidrológicos em bacias de rios intermitentes no semiárido mineiro - Roberto Cezar de Almeida Monte-mor (2012)
The understanding of the hydrological behaviour of the Brazilian semiarid region, in general, and of the Minas Gerais semiarid region, in particular, is of fundamental importance. The lack of hydrological data of small Brazilian basins generates uncertainties that may affect the management of water resources and the water availability assessment, limiting its uses. In the intermittent basins of the Minas Gerais semiarid area there are few hydrometeorological information and the limitations for a proper water resources management are due to the lack of high quality observations, the relatively scarce economic resources and the infrequent occurrence of climatic events. In this study data from a hydrological monitoring that was conducted for 30 months are analyzed in order to acquire and expand the knowledge about the spatial and temporal behaviour of processes in the representative watershed named Teixeirão, a tributary of the Jequitinhonha River. The acquired data subsidize the evaluation of the hydrological phenomena monitored, and the following annual averages were obtained: rainfall of 725.52 mm, potential evapotranspiration of 1976.92 mm and actual evapotranspiration of 1032.19 mm; interception losses of 16.6% from the total precipitation. The runoff coefficients obtained were 6.30% (2009/2010) and 3.72% (2010/2011). Infiltration tests and soil water monitoring have been also carried out. Analysis of the soil moisture spatial and temporal variability were performed in two subareas, which allowed the determination of their representative points considering minimum, average and maximum soil moisture. The collected hydrological data supported the use of two rainfall-runoff models (adapted Rio Grande and MORECS). There were presented issues related to uncertainties in the observed discharge values. The values of the Nash-Sutcliffe coefficient related to the Rio Grande model simulations are adequate for the calibration period, only reasonable when considering the whole monitoring period and satisfactory to simulate flows in a neighbour intermittent watershed (Teixeirinha). The MORECS model integrated soil moisture results are adequate, but the discharge values were much higher than those observed. It is concluded that the implementation of the mentioned monitoring system enabled a better understanding of the hydrological conditions of the Teixeirão watershed, especially the related to soil moisture behaviour. It is recommended to get additional points of the stage-discharge relationship of the Teixeirão and Teixeirinha water courses, to monitor the groundwater flow in their alluviums and to verify the performance of a hydrological model that incorporates the formulation of the MORECS model in the structure of the adapted Rio Grande model.